Penerapan Reliability Centered Maintenace untuk Pemeliharaan Mesin Crane di PT Pelindo - Silaban, Levi; Tampubolon, Jusra Tampubolon (Program Studi Teknik Mesin, Universitas HKBP Nommensen, Medan, 2025)
This study aims to analyze the implementation of Reliability Centered Maintenance (RCM) in the maintenance of crane machines at PT Pelindo. Cranes play a vital role in port loading and unloading activities, making operational reliability essential for smooth logistics operations. The RCM approach is used to identify critical components based on potential failures, their impact on operations, and the effectiveness of maintenance actions. Data were collected through observation, interviews, documentation, and questionnaires, and analyzed using Failure Mode Effect Analysis (FMEA), Mean Time Between Failure (MTBF), Mean Time To Repair (MTTR), and Availability. The results indicate that components such as the contactor, carbon collector, and motor hoist/gearbox have the highest Risk Priority Number (RPN), requiring prioritized maintenance. The MTBF value of 317.687 hours reflects a relatively high level of machine reliability, while the MTTR of 3.25 hours demonstrates repair efficiency. The implementation of RCM has proven effective in improving reliability, reducing downtime, and minimizing maintenance costs. The study recommends enhancing preventive and predictive maintenance, as well as training technicians to efficiently detect and manage failures. Keywords: Reliability Centered Maintenance, crane, maintenance, FMEA, MTBF, MTTR